Summative Effects of Vascular Risk Factors on the Progression of Alzheimer Disease. Issue 1 (6th October 2019) - Lee, Wei‐Ju; Liao, Yi‐Chu; Wang, Yen‐Feng; Lin, Yung‐Shuan; Wang, Shuu‐Jiun; Fuh, Jong‐Ling
Abstract : OBJECTIVES: To investigate the summative effects of vascular risk factors (VRFs) on the progression of Alzheimer disease (AD). DESIGN: Longitudinal follow‐up cohort study. SETTING: AD patients from two teaching hospitals in Taiwan with 3‐year follow‐ups. PARTICIPANTS: A total of 330 AD patients with a mean age of 80.7 years, a mean Mini‐Mental State Examination (MMSE) score 18.7, and a mean Clinical Dementia Rating Sum of Boxes (CDRSB) score of 6.9. MEASUREMENTS: All patients completed a clinically functional assessment and a neuropsychological test battery at baseline and yearly follow‐ups. The VRF burden was combined into a summative VRF index at baseline (ie, having one, two, or more VRFs); VRFs included coronary heart disease, cardiac arrhythmia, hypertension, cerebrovascular disease, diabetes mellitus, obesity, smoking, and physical inactivity. The generalized estimating equation (GEE) method was used to analyze the correlations between the VRFs and longitudinal MMSE and CDRSB changes. RESULTS: The results of the GEE adjusted for age, years of education, sex, disease duration, baseline MMSE score, time, apolipoprotein E (APOE) ε4 carrier status, use of medications (acetylcholinesterase inhibitors or N‐methyl‐D‐aspartate receptor antagonists), and hospitalization rates and showed that patients with more than three VRFs had more rapid cognitive decline than patients without VRFs (MMSE, P = .02; CDRSB, P = .001) as well as patients with three or fewer VRFs (MMSE, P = .009; CDRSB, P = .02). Subsequent analyses of APOE ε4 carriers with more than three VRFs also showed their more rapid cognitive decline compared with patients without VRFs (MMSE, P = .02; CDRSB, P = .001) and patients with three or fewer VRFs (MMSE, P = .009; CDRSB, P = .02), but no significant difference was found in APOE ε4 noncarriers. CONCLUSION: Multiple VRFs have summative effects on the progression of AD, especially in APOE ε4 carriers. J Am Geriatr Soc 68:129–136, 2019